2018
DOI: 10.1113/jp275688
|View full text |Cite
|
Sign up to set email alerts
|

Identification of uterine pacemaker regions at the myometrial–placental interface in the rat

Abstract: Key Points Coordinated contraction of the uterine smooth muscle is essential to parturition.Histologically and physiologically defined pacemaker structures have not been identified in uterine smooth muscle.Here we report combined electrophysiological and histological evidence of zones associated with pacemaker activity in the rat myometrium.Our method relies crucially on the integration of histological and electrophysiological data in an in silico three‐dimensional reconstruction of the rat myometrium at 10 μm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…This phenomenon may relate to previous reports that anchoring villi (connecting the chorionic plate to the uterine wall) are contractile, because such contractility would assist in maintaining the shape of the placenta as the wall contracts [7]. It may also be related to the myometrial-placental pacemaker zone that has recently been identified in rats [49]. It is likely that such utero-placental contractions may have previously been identified as Braxton Hicks contractions involving the whole uterine wall (S3C Fig), or localized uterine contractions on ultrasound [50] and MRI [50,51], which have been associated with transient reductions in both uterine blood flow [52] and placental oxygenation [37].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This phenomenon may relate to previous reports that anchoring villi (connecting the chorionic plate to the uterine wall) are contractile, because such contractility would assist in maintaining the shape of the placenta as the wall contracts [7]. It may also be related to the myometrial-placental pacemaker zone that has recently been identified in rats [49]. It is likely that such utero-placental contractions may have previously been identified as Braxton Hicks contractions involving the whole uterine wall (S3C Fig), or localized uterine contractions on ultrasound [50] and MRI [50,51], which have been associated with transient reductions in both uterine blood flow [52] and placental oxygenation [37].…”
Section: Discussionsupporting
confidence: 63%
“…We also need to understand what triggers the contractions: is it a reduction in oxygenation or an increase in pressure within the placenta? Are the contractions initiated in the myometrium of the placental bed [49] or by the anchoring villi [7]? The rate of detection of contractions was higher in PEs than in HCs, but longer sampling in more participants is required to be confident of any difference.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may relate to previous reports that anchoring villi (connecting the chorionic plate to the uterine wall) are contractile, since such contractility would assist in maintaining the shape of the placenta as the wall contracts [7]. It may also be related to the myometrial-placental pacemaker zone that has recently been identified in rats [49]. It is likely that such uteroplacental contractions may have previously been identified as Braxton Hicks contractions involving the whole uterine wall (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…We also need to understand what triggers the contractions: is it a reduction in oxygenation, or an increase in pressure within the placenta? Are the contractions initiated in the myometrium of the placental bed [49] or by the anchoring villi [7]? The rate of detection of contractions was higher in PEs than HCs, but longer sampling in more subjects is required to be confident of any difference.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal survival of all pups would be facilitated if the placentae of pups closest to the cervix became detached from the uterine wall earlier in the labour process, while those closer to the oviduct remained firmly attached to the uterine wall. It is unclear from the study of Lutton et al , whether and to what extent this might have occurred. In other words, a sophisticated contraction gradient along the uterus might be required.…”
mentioning
confidence: 99%